Community Empowerment Program Through Transformation Process In Samarinda Islamic High School - Nurhayati Nurhayati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
The main task of universities in developing science is not only teaching and research, but also community empowerment. In this study, the question is how the Samarinda Islamic High School in carrying out community empowerment activities using social transformation or change? The type of research in this study is descriptive analytical research, because the researcher describes the transformation or social change first and then analyzes the social changes carried out by the Islamic High School. With the method of transformation or social change in the form of stages of invention, diffusion and consequences. the process of social change with these three, the Islamic High School conducts a study first by looking at and studying the behavior of the community in relation to change. Social change is a process where there is a change in the structure and function of a social system. These changes occur as a result of the inclusion of reform ideas so that they are beneficial to the community. Social change in society is not an outcome or a product but a process. In the end, the change is a joint decision taken by community members. These changes occur as a result of the inclusion of reform ideas so that they are beneficial to the community. Social change in society is not an outcome or a product but a process. In the end, the change is a joint decision taken by community members. These changes occur as a result of the inclusion of reform ideas so that they are beneficial to the community. Social change in society is not an outcome or a product but a process. In the end, the change is a joint decision taken by community members.